Intense X-ray sources based on Compton scattering in laser electron storage rings - Gladkikh, P.I.; Karnaukhov, I.M.; Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2002)
The main problem of the designing of intense X-ray sources based on Compton scattering in laser-electron storage ring is associated with large steady-state electron beam energy spread. In paper the principles of the development of compact storage ring lattice with large RF-acceptance and negligible chromatic effects at interaction point are considered. The storage ring with electron beam energy over the range 100-400 MeV that allows generating intense VUV from bending magnets, X-ray up to 280 keV with rate up to 10¹⁴ photons /s and γ-beam up to 2.8 MeV for neutron generation on beryllium target is proposed.